Research on the generation of food safety network public opinion-Taking the Chinese Mouse Head Duck Neck Incident as an example. - Wei Yang; Jiayin Pei; Zheyu Lin (PLoS ONE, 2025)
In recent years, the frequent occurrence of food safety incidents has posed a serious threat to people's lives and properties, and triggered heated discussions in the whole society. If the relevant departments shirk each other's responsibilities or deceive the public in handling the incident, it will further lead to the generation of network public opinion, which will have an impact on the stability of the society and the credibility of the government. In order to study the generation of food safety network public opinion, this article takes the sudden "mouse head and duck neck" incident in a university in Jiangxi Province, China as an example, and combines text mining with grounded theory. Firstly, the LDA topic clustering model is used to identify six main concerns (topics) of the public during the public opinion period, and the topic words and words with high TF-IDF values under each topic is counted. Based on this, the grounded theory method is used for three-level coding, and then a network public opinion generation model is constructed. It was found that the four main categories of national subjects, public's responses, value orientations, and news media play an important role in the generation process of network public opinion. These findings not only provide a reference for the governance of food safety public opinion in China, but also shed light on public opinion management in other countries, especially when responding to food safety incidents of general significance.